Exergoeconomic evaluation of a system driven by parabolic trough solar collectors for combined cooling, heating, and power generation; a case study. (1st February 2020) - Haghghi, Maghsoud Abdollahi; Mohammadi, Zahra; Pesteei, Seyed Mehdi; Chitsaz, Ata; Parham, Kiyan
Abstract: An exergoeconomic assessment of a combined cooling, heating, and power generation system is conducted for summer air conditioning for the school of engineering at Urmia University in Iran. The proposed application comprises of parabolic trough solar collectors integrated with an organic Rankine cycle and two single-effect absorption chillers. The novelty of the paper relies on considering the real energy load and solar radiation for the exergoeconomic analysis. Hence, three solar radiation operational modes are simulated, which includes low (solar mode), high (solar and storage mode), and no radiation (storage mode) during the day. The effects of the three vital parameters, including Day numbers, organic Rankine cycle pump inlet temperature, and organic Rankine cycle turbine inlet pressure on several variables are examined. The results illustrated that the highest cooling, heating, and electrical power loads of the building during summer time are 896.9 kW, 228.5 kW, and 1500 kW, respectively. Furthermore, the cost per unit exergy of the generated power for the above-mentioned modes are 11.44 $/GJ, 10.27 $/GJ, and 15.47 $/GJ, respectively. It was concluded that these values decrease by 16.4, 18.4, and 11.9% point as a result of the overall system establishment. Highlights: Exergoeconomic study is performed of a parabolic trough collector-based CCHP system. Analysis is conducted in summer for the school of engineering at Urmia University. Study is carried out in three solar radiation operational modes during the day. On average the cost per unit exergy of system on 160th day of the year is 10.5 $/GJ. On average the cost rate of system's products on 160th day of the year is 120.8 $/h.